Peran Guru Pendidikan Islam Dalam Membentuk Sikap Kepemimpinan Siswa di SMA PAB 4 Sampali - Widya, Ratih; M, Mahariah; M, Muslem (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research aims to describe the role of PAI teachers in forming students' leadership attitudes at PAB 4 Sampali High School, what factors support the formation of students' leadership attitudes at PAB 4 Sampali High School, and what obstacles are faced by PAI teachers in forming high school students' leadership attitudes. PAB 4 Sampali.This research uses qualitative research. This research data is data resulting from field observations, interviews and document studies. There are also data sources consisting of PAI teachers, school principals and students of SMA PAB 4 Sampali. Data analysis in this research uses Miles and Huberman data analysis which consists of data reduction, data presentation, and drawing conclusions. The technique for checking the validity of the data is using data triangulation techniques which consist of triangulation of sources, techniques and time. From this research, it was found that the role of PAI teachers in forming students' leadership attitudes has played a very good role in accordance with their role as PAI teachers. There are supporting factors for the role of Islamic Religious Education teachers in forming student leadership attitudes at SMA PAB 4 Sampali, such as the school curriculum which is also relevant, the principal and other teachers who are very supportive and involved, as well as support from the family environment, obstacles experienced in implementing This was triggered by several things, namely the influence of social media, lack of concern from parents at home regarding their children's education, completeness of school facilities and infrastructure, and lack of motivation among students to develop better.